Active Controlling of Cabin Benzene from Front Dashboard for Driver Passenger Safety. (2021) - Sudhir Kumar, V.; Ponvaanan, P.; Srinivasan, M.; Naveen Kumar, A.
Highlights: F Car's interior toxic gas detection results in deformation on dashboards, seats and other plastics on hot weather conditions. Hence it is necessary to indicate the value of gas concentration in car's interior. When the benzene level is increased, the car blows air from environment to car's interior and the exhaust fan expels out car's benzene gas to the environment. When the ppm level is decreased to normal level, the exhaust fan and car blower stops. Abstract: The amount of toxic benzene gas is increasing rapidly due to development in plastic industries and also due to more amount of vehicle exhaust & gasoline production all over the world. These results not only develop the wealth of a nation, but it seriously affects the environment, human and other living beings. Through this project. We can detect high toxic benzene gas in the car cabin and industry on working condition. By this detection of benzene gas, exposure of passengers to such toxic gases inside vehicle cabin is considerably decreased. In this work, focus has been on car's interior toxic gas detection due to which deformation taken place on dashboards, seats and other plastics on hot weather condition. By this it is also necessary to indicate the value of gas concentration in car's interior in ppm reading. Thereby, a battery is fixed inside a car, and a GSM module and Arduino is powered. MQ135 gas sensor detects the benzene level inside of the car and it will be projected on an LCD display. When the benzene level is increased above 300 ppm, a message will be sent to the mobile as "GAS LEVEL HIGH" and we command a text through mobile as "*START#", by this the exhaust fans and car blower starts, where the car blower blows air from environment to car interior cabin and the exhaust fans expels out the car's interior benzene gas to the environment. When the ppm level is decreased to normal level which is below 286 ± 14 ppm, a message would be received through mobile phone as "GAS LEVEL LOW" and we command a text as "*STOP#", thus within 7 min the ppm level decreases from 300 to 286 ± 14 ppm. By this, the exhaust fans and car blower stops. Hence higher level of safety is ensured from the toxic gas produced inside a car cabin and instead of manually opening the door glass to reduce the benzene level.